New media and the problematic of public opinion’s industry - Mebni, Noureddine; Aissaoui, Tayeb; Loucif, Amar (Journal of Human Sciences, 2022)
This topic is concerned with talking about new transformations in the field of public opinion industry and monitoring the most prominent features of these transformations and their impact on traditional media in terms of the nature of the contributors to forming public opinion, the means relied upon and the possibilities available for that. According to Bourdieu, that we have moved from an ideology based on a political, cultural or religious basis to an ideology on a communicative basis. Based on this proposition, the importance of this issue appears through the influence of information and communication technologies on the standards of social interaction at several levels. Communication between people is no longer that difficult and complex because it has become characterized by more flexible and easy characteristics that make it an indispensable means for large groups within Society, until it became an essential factor in making public opinion and directing it strongly and effectively.